Model Pengembangan Media Pembelajaran Berbasis Kecerdasan Buatan (AI) di Madrasah Ibtidaiyah - Bariroh, Hurril; Ashari, Ashari (Universitas Muhammadiyah Ponorogo, 2025)
Integrating Artificial Intelligence (AI) into learning media must be aligned with the learning component to function optimally in teaching and learning activities. The study analyzes urgency, selection criteria, and procedures for developing AI-based learning media. This study employs a qualitative approach using a library research method. Data were collected through a systematic review of books, journal articles, and other credible academic sources relevant to the research topic. The research instrument in this research is documentation, which involves identifying, selecting, and interpreting relevant written materials. Data analysis used content analysis techniques to identify patterns, themes, and key concepts related to the research focus. The results of this study show that the importance of AI-based learning media in Madrasah Ibtidaiyah can be reviewed from an independent curriculum perspective and a technology perspective. AI-based learning media criteria can be seen from the extent to which they are compatible with learning system components, such as learning objectives, learning materials, learning media, teachers, and educators. Procedures include analyzing the conditions and needs of learning components, formulating AI-based learning media designs, and implementing such designs. The implications of this research suggest that when developed systematically, AI-based learning media can enhance effectiveness.